Expression of Oxidative Phosphorylation Complexes and Mitochondrial Mass in Pediatric and Adult Inflammatory Bowel Disease. (6th January 2022) - Schneider, Anna M.; Özsoy, Mihriban; Zimmermann, Franz A.; Brunner, Susanne M.; Feichtinger, René G.; Mayr, Johannes A.; Kofler, Barbara; Neureiter, Daniel; Klieser, Eckhard; Aigner, Elmar; Schütz, Sebastian; Stummer, Nathalie; et al.
Abstract : Introduction . Inflammatory bowel disease (IBD), which includes Crohn's disease (CD) and ulcerative colitis (UC), is a multifactorial intestinal disorder but its precise etiology remains elusive. As the cells of the intestinal mucosa have high energy demands, mitochondria may play a role in IBD pathogenesis. The present study is aimed at evaluating the expression levels of mitochondrial oxidative phosphorylation (OXPHOS) complexes in IBD. Material and Methods . 286 intestinal biopsy samples from the terminal ileum, ascending colon, and rectum from 124 probands (34 CD, 33 UC, and 57 controls) were stained immunohistochemically for all five OXPHOS complexes and the voltage-dependent anion-selective channel 1 protein (VDAC1 or porin). Expression levels were compared in multivariate models including disease stage (CD and UC compared to controls) and age (pediatric/adult). Results . Analysis of the terminal ileum of CD patients revealed a significant reduction of complex II compared to controls, and a trend to lower levels was evident for VDAC1 and the other OXPHOS complexes except complex III. A similar pattern was found in the rectum of UC patients: VDAC1, complex I, complex II, and complex IV were all significantly reduced, and complex III and V showed a trend to lower levels. Reductions were more prominent in older patients compared to pediatric patients and more marked in UC than CD. Conclusion . A reduced mitochondrial mass is present in UC and CD compared to controls. This is potentially a result of alterations of mitochondrial biogenesis or mitophagy. Reductions were more pronounced in older patients compared to pediatric patients, and more prominent in UC than CD. Complex I and II are more severely compromised than the other OXPHOS complexes. This has potential therapeutic implications, since treatments boosting biogenesis or influencing mitophagy could be beneficial for IBD treatment. Additionally, substances specifically stimulating complex I activity should be tested in IBD treatment.